ANTLR-based flattening conversion method for AltaRica 3.0 - CHEN SHUO; HU JUN (2019)
The invention relates to an ANTLR-based flattening conversion method for AltaRica 3.0, which mainly comprises the following two parts: 1, compiling an ANTLR syntax file of the AltaRica 3.0, and obtaining a corresponding abstract syntax tree; and 2, operating the syntax tree by using a designed algorithm, and obtaining a flattened file from an input AltaRica 3.0 hierarchical file of a certain system. The method is an important solution for converting the hierarchical structure of the AltaRica 3.0 model into the flattened structure, safety analysis can be carried out on the AltaRica model of a certain system by converting the hierarchical structure into the flattened structure, and the process is very important in the field of safety critical systems. 基于ANTLR的AltaRica 3．0的扁平化的转化方法，主要包括两个部分内容：其一，编写AltaRica 3.0的ANTLR语法文件，获取相应的抽象语法树；其二，利用设计的算法对语法树进行操作，由输入的某个系统的AltaRica 3.0层次化文件获取扁平化的文件。本发明是解决AltaRica 3.0模型层次化结构转化为扁平化结构的重要解决方案，通过转化为扁平化的结构，可以对某个系统的AltaRica模型进行安全性分析，在安全关键系统领域，这个过程是非常重要的。